PENGEMBANGAN MODEL PEMBINAAN DISIPLIN PESERTA DIDIK UNTUK MENCEGAH PELANGGARAN TATA TERTIB DI SEKOLAH - Canra Muhammad Kadfi; Dadan Samsul Badar; Al Juska Sasni Akbar; Siti Uswatun Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the high incidence of student violations of school rules, particularly tardiness, despite the existence of a disciplinary guidance system in schools. This issue indicates that the current guidance has not been fully effective in fostering students’ awareness and responsibility. This study aims to develop a more effective student discipline guidance model through a Preventive-Collaborative Reflective-Based approach (PDPR). The method used is Research and Development (R&D) with stages including needs analysis, design, development, expert validation, and limited trials. The research subjects consisted of 17 tenth-grade students. The instruments used included questionnaires, interviews, expert validation sheets, and student violation reflection sheets. Data were analyzed using quantitative descriptive techniques in the form of percentages and qualitative analysis through the categorization of students’ reflection results. The results showed that the most dominant violation was tardiness, with a percentage of 76.5%, which was mostly caused by internal student factors. Expert validation results indicated that the PDPR model achieved a feasibility level of 95.62%, categorized as highly feasible. The limited trial showed that students were able to identify violations, understand their causes and impacts, and formulate improvements, particularly in time management aspects. The PDPR model is considered capable of supporting discipline guidance that is more educational, preventive, and oriented toward students’ reflective awareness.